2014
DOI: 10.1590/1516-4446-2013-1187
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid psychiatric disorders and stages of change in cannabis-dependent, treatment-seeking patients

Abstract: The high prevalence of concurrent psychiatric disorders in cannabis-dependent patients should serve as a stimulus for early screening and treatment of such disorders. Health care professionals should be aware of the magnitude of this association to increase the level of motivation in cannabis-dependent patients with severe concurrent psychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(20 reference statements)
1
1
0
Order By: Relevance
“…The highest percentage of DSM-5 Spectrum Psychotic Disorder (33%) and the lowest percentage of trauma & stressor-related disorder (1.8%) were discovered. This was somewhat similar to the study conducted by Sarkar et al, which discovered that 34% had substance dependence and 53% had psychotic illness [12]. According to a similar study conducted in Brazil in 2010, 22.5 percent of the population suffered from depression, 11% from generalised anxiety disorder, 8.8 percent from panic disorder, and 8.8 percent from schizophrenia, with the remaining 31 percent only having cannabis dependence.…”
Section: Discussionsupporting
confidence: 87%
“…The highest percentage of DSM-5 Spectrum Psychotic Disorder (33%) and the lowest percentage of trauma & stressor-related disorder (1.8%) were discovered. This was somewhat similar to the study conducted by Sarkar et al, which discovered that 34% had substance dependence and 53% had psychotic illness [12]. According to a similar study conducted in Brazil in 2010, 22.5 percent of the population suffered from depression, 11% from generalised anxiety disorder, 8.8 percent from panic disorder, and 8.8 percent from schizophrenia, with the remaining 31 percent only having cannabis dependence.…”
Section: Discussionsupporting
confidence: 87%
“…Other studies found lifetime cannabis use to be associated with common mental health disorders (e.g., anxiety, depressive mood) (aOR: 2.83, p < 0.01, n = 234) [117] and correspondingly associated with panic disorder (PR: 3.31, p = 0.001, n = 1081) [118] among individuals attending health‐care units. However, no association between comorbid psychiatric disorders (e.g., anxiety and depression) and age at first cannabis use or quantity of cannabis used was confirmed among patients ( n = 80) seeking treatment for cannabis‐related problems at an outpatient university clinic [119].…”
Section: Resultsmentioning
confidence: 99%